Working Women’s Wellness (Well-Being) and Their Performance at Work in India - Mantri, Janhavi Manish (Digital Repository of Theses, 2025)
This research explored how different dimensions of wellness influence the workplace performance of women professionals in India’s corporate sector. Grounded in the Job Demands-Resources (JD-R) framework and comprehensive wellness models, the study investigated the role of physical, emotional, occupational, social, intellectual, and spiritual well-being in shaping professional outcomes. The central objective was to investigate whether enhanced wellness positively influences job performance, engagement, and resilience in demanding work environments. The study adopted a mixed-methods design, combining quantitative surveys with qualitative interviews conducted among a purposively selected group of working women from key metropolitan cities in India. The survey measured wellness using standardized scales, while performance was evaluated based on self-assessments and feedback from supervisors where available. The qualitative phase provided deeper insights into the lived experiences, stressors, and coping mechanisms of participants. Findings revealed a strong correlation between overall wellness and perceived job performance. Emotional and occupational wellness emerged as the most significant predictors of productivity, creativity, and adaptability at work. Social support systems and organizational culture played a crucial mediating role in maintaining wellness levels. Moreover, women who reported higher levels of work-life integration and access to wellness initiatives exhibited greater motivation and lower burnout rates. The study underscored that wellness is not a singular or static concept but a dynamic, multidimensional construct that evolves with personal and professional life stages. In particular, the Indian context—with its unique socio-cultural expectations from women—necessitated a broader understanding of wellness that includes familial obligations and societal norms. Based on the findings, the study recommended that Indian organizations adopt a holistic wellness framework tailored to women’s needs, including flexible work policies, mental health support, mentorship programs, and inclusive workplace practices. These strategies are not only vital for enhancing women’s well-being but also for strengthening organizational performance and gender equity in the workplace. This research contributed to the growing body of literature on workplace wellness and offered practical insights for HR practitioners, policymakers, and leaders striving to build thriving, resilient workforces in India.